1975
DOI: 10.1159/000251361
|View full text |Cite
|
Sign up to set email alerts
|

Provocation Tests with Antiphlogistica and Food Additives in Recurrent Urticaria

Abstract: 100 patients (53 women, 47 men) suffering from recurrent urticaria were tested with different food additives such as 8 dye additives, 7 preservatives and 7 antiphlogistica. In total did 62 patients react with urticaria and/or angio-oedema. 39 patients had reactions to two or more substances while 23 patients reacted to only one substance. Reactions were induced most frequently by aspirin (27/80), dextropropoxyphene (11/45) and the azo dyes tartrazin (20/96) and sunset yellow (13/86). Asthmatic symptoms occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 12 publications
2
19
1
Order By: Relevance
“…Acute urticaria is much more likely to be caused by food allergy than CU. However, there is a subgroup of patients with RCIU with food-additive-evoked urticaria [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…Acute urticaria is much more likely to be caused by food allergy than CU. However, there is a subgroup of patients with RCIU with food-additive-evoked urticaria [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…Several authors have published results of a diet free of additives in chronic urticaria [1,[4][5][6][7][8][9][10]12,13]. Obviously, their success rate is very different (ranging from 33 to 87%).…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature indicates that in the particular centers this percentage varied from 21 to 75 [Doeglas, 1975], Using provocation tests some of the authors observed reactions in 35 of 52 patients with urticaria [Michaelsson and Juhlin, 1973], in 16 of 50 patients [Doeglas, 1975], in 62 of 100 [Thune and Granholt, 1975] and in 66 of 111 patients [ War in and Smith, 1976]. Comparison of these results is difficult since the challenge test batteries of the particular authors differed, including in some cases even penicillin and yeast extract [Warm and Smith, 1976], Among the subjects reacting to the battery an appropriate diet brought remission or noticeable improvement in 62% [Thune and Granholt, 1975], in 75% [Warin and Smith, 1976] or in 81% of patients [/toss et al, 1976].…”
Section: Discussionmentioning
confidence: 99%